Modelling corrosion rate of biodegradable magnesium-based alloys: the case study of Mg-Zn-RE-xCa (x = 0, 0.5, 1.5, 3 and 6 wt%) alloys - Bakhsheshi-Rad, H. R. (Elsevier, 2016)
The ternary Mg-Zn-RE and the quaternary Mg-Zn-RE-xCa (x = 0.5, 1.5, 3 and 6 wt%) alloys are evaluated in term of their corrosion rate both experimentally and theoretically. According to the electrochemical tests, the quaternary Mg-Zn-RE-0.5Ca alloy possess a lower corrosion current density (icorr) and higher charge transfer resistance (Rt) compared to the ternary Mg-Zn-RE alloy. However, as the Ca increases, icorr and Rt tend toward the higher and lower values, respectively. Immersion tests also show that the addition of 0.5 wt% Ca decreases the corrosion rate of the Mg-Zn-RE alloy. This despite the fact that with increasing the Ca content to 6 wt% a significant increase occurs in the corrosion rate as a result of the galvanic coupling effect. The study also defines a new reliability simulation framework to predict the corrosion behavior of the Mg-based alloys using gene expression programming (GEP) tool. For this purpose a colossal database is collected from the literature and all of the parameters affecting the corrosion rate are introduced to the GEP model. Two case study on the ternary Mg-Zn-RE and the quaternary Mg-Zn-RE-xCa (x = 0.5, 1.5, 3 and 6 wt%) alloys are also conducted to evaluate the accuracy of the presented GEP model. according to the results obtained, the maximum error of the presented model in the predicting corrosion rate was close to 0.5 mm/yr which is promising result.